How 21st century skills can be taught: Design and implementation of an undergraduate course for prospective teachers - GÜVEN, Meral; Durmuş, Abdulkadir (Jurnal Cakrawala Pendidikan, 2025)
21st century skills constitute one of the most salient foci within contemporary educational discourse. However, the persistent absence of a detailed and systematic curriculum addressing the pedagogy of these skills remains a significant challenge for teacher education.  Employing a mixed-methods study, this study aims to develop and implement a course curriculum that focuses on teaching 21st century skills to prospective teachers. Data were rigorously collected through document and content analyses, semi-structured interviews, and a pre- and post-administration of “The scale for identifying perceptions of having 21st century skills,” developed and validated to determine the significance of the difference. The study encompasses three distinct phases: needs analysis process, design and piloting of the course, and implementation of the developed course with prospective teachers. The study participants were 18 academicians affiliated with diverse faculties of education from various universities, and a total of 73 pre-service teachers (56 for piloting and 17 for real implementation). The needs analysis conclusively indicated a clear demand for such a course. Consequently, a modular-based undergraduate course was developed and implemented over 28 weeks (14 weeks for the pilot and 14 weeks for the real implementation), aiming to teach how to teach 21st century skills grounded in the principles of progressivism and constructivism. The course delivery was structured around micro-teaching activities. Findings indicate that the course had a positive impact on pre-service teachers’ awareness and perceived ability to teach 21st century skills, highlighting the value of a dedicated, practical curriculum in teacher education.